Perancangan Quality Plan dalam Sistem Manajemen Mutu di sebuah Pabrik Kertas - Yonathan Stanley Suryahadi; I Nyoman Sutapa (Jurnal Titra, 2017)
This Paper Company is a manufacturing company at the field of thin paper industry. At the beginning, this company did not have the quality assurance to final product which has the standard of the quality management system. This study represents that the company doesn't have the Quality Plan to the product. The Quality Plan become the main concern to assure the product quality until they are distributed to the customer. This study is meant to design the Quality Plan for the company management system. It will be divided into three parts; first, the inspection of the raw and chemical materials, second, the inspection of the production process, and the final is the inspection of the output jumbo roll. This first inspection is done five times, the second inspection will done in twelve times, and the final process will be done in one process only.